A critical analysis of the right to clean environment in terms of the South African Constitution - Mdhluli, P. N. (My University, 2012)
This study focuses on the right of “everyone to have access to an environment that is not harmful to their health or well-being; and to have the environment protected, for the benefit of present and future generations, through reasonable legislative and other measures that prevent pollution and ecological degradation, promote conservation and secure ecologically sustainable development and use of natural resources while promoting justifiable economic and social development”. This study discusses the government policies, domestic legislations and international law.
Thesis (LLM. (Development and Management Law)) -- University of Limpopo, 2012
Keywords: Clean environment; Human rights; Environmental law -- South Africa; Environmental management -- South Africa; Environmental protection -- South Africa; Human rights -- South Africa